E-COMMERCE PRODUK KERAMIK: (Studi Kasus: FAYYOLA KERAMIK) - Uro Abdurohim; Asri Islamiyanti (Jurnal Teknologi Informasi dan Komunikasi, 2021)
The Fayyola Ceramics shop use a manual system so customer have to come directly to the store to buy or ask about products. If you only rely on the sales system in this way, it will take time so that customer have to wait and this has an impact on slow sales due to the absence of product promotion. With the web-based e-commerce application, it is hoped that it can help. Ceramic entrepreneurs market their product and consumers can access information on products being sold and place ordersfor products. In making this application using dreamweaver, PHP and MySQL as a database. The existence of this application is expected to expand the marketing reach of the Fayyola Ceramics Store and the UML method used to analiyze the design of e-commerce application.